(untitled) (Environment & Health, 2026)
Introduction. Rehabilitation treatment is one of the key stages of health care delivery, aimed at restoring or improving physical, cognitive, and functional abilities after injury, illness, or surgical interventions. International clinical guidelines clearly regulate the need for nutritional screening of all hospitalized patients, followed by risk assessment and dietary correction in accordance with the patient’s clinical condition. Assessment of satisfaction with the organization of nutrition is an important indicator of the quality of nutritional support, as it makes it possible to identify discrepancies between regulatory requirements and actual food practices. The relevance of this study is determined by the need to improve food quality and to adapt menus to the actual needs of military personnel undergoing inpatient rehabilitation. Purpose. To assess the level of satisfaction of military personnel with the organization of food during rehabilitation treatment and to determine the factors affecting eating habits, the feeling of satiety, and the overall assessment of diet quality. Materials and methods. The study was conducted within the framework of a planned research project of the Ukrainian Military Medical Academy using an anonymous survey of servicemen undergoing rehabilitation at a military medical rehabilitation center. The questionnaire included items on satisfaction with food organization, quality and variety of dishes, and suggestions for menu improvement. Percentage distributions, Student’s t-test, and Spearman’s correlation coefficient (p